The possible impact of pre-transfusion laboratory interference - Luís Moura; Liliana Fonseca; Emanuel Rodrigues; Rui Lobo; Arnaldo Brito; Mariana Costa (Millenium)
Introduction: Pre-transfusion tests allow the detection of clinically significant antibodies and the prior compatibility of units to be transfused.